2021
DOI: 10.1101/2021.05.05.442662
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Telomeric 8-Oxoguanine Drives Rapid Premature Senescence In The Absence Of Telomere Shortening

Abstract: SUMMARYOxidative stress is a primary cause of cellular senescence and contributes to the pathogenesis of numerous human diseases. Oxidative damage to telomeric DNA is proposed to trigger premature senescence by accelerating telomere shortening. Here we tested this model directly using a precision tool to produce the common base lesion 8-oxo-guanine (8oxoG) exclusively at telomeres in human fibroblast and epithelial cells. A single induction of telomeric 8oxoG is sufficient to trigger multiple hallmarks of p53-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 81 publications
(108 reference statements)
2
12
0
Order By: Relevance
“…In addition to being hard to repair, telomeric DNA is hypersensitive to oxidative DNA damage, a phenomenon recently named TelOxidation 22 . Oxidative stress reportedly both induces tDD without telomere shortening and accelerates telomere shortening [23][24][25][26] by inhibiting telomerase 27 and disrupting the recognition by telomere-binding proteins, which contributes to telomere uncapping 22,28 .…”
mentioning
confidence: 99%
“…In addition to being hard to repair, telomeric DNA is hypersensitive to oxidative DNA damage, a phenomenon recently named TelOxidation 22 . Oxidative stress reportedly both induces tDD without telomere shortening and accelerates telomere shortening [23][24][25][26] by inhibiting telomerase 27 and disrupting the recognition by telomere-binding proteins, which contributes to telomere uncapping 22,28 .…”
mentioning
confidence: 99%
“…Photosensitizer di-iodinated malachite green (MG2I) dye (D) produces 1 O2 when bound to a fluorogen activating peptide (FAP) fused with telomeric protein TRF1, and then activated with 660 nm light (L) 33,34 . We previously demonstrated that acute production of telomeric 8oxoG in non-diseased human BJ hTERT fibroblasts (BJ FAP-TRF1) increased senescent cells just 4 days after dye and light (DL) exposure 16 . To determine the role of BER processing in modulating telomeric 8oxoG-induced senescence, we disrupted OGG1 and MUTYH genes in BJ FAP-TRF1 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Using a chemoptogenetic tool to selectively produce 8oxoG at telomeres, we demonstrated that the chronic and persistent formation of telomeric 8oxoG in HeLa LT cancer cells accelerates telomere shortening and drives hallmarks of telomere crisis including dicentric chromosomes 15 . More recently, we showed that acute production of telomeric 8oxoG in nondiseased human fibroblasts and epithelial cells triggers rapid telomere dysfunction and p53mediated cellular senescence in the absence of telomere shortening 16 . We found 8oxoG induces telomere dysfunction by causing replication stress at telomeres, consistent with reports that 8oxoG can stall replicative polymerases 17 .…”
Section: Introductionmentioning
confidence: 96%
“…This phenomenon is perhaps best explained by the activation of a specific homology directed repair pathway known as mitotic DNA synthesis (MiDAS), which is a form of break-induced replication activated in response to replicative stress at loci difficult to replicate, such as telomeres ( 39 , 40 , 41 ). It was recently demonstrated that the highest levels of basal telomere MiDAS occur in cells with the longest telomeres and that 8-oxo-dG in telomere regions activates MiDAS instead of shortening telomeres, which results in their fragility ( 9 , 42 ). This mechanism in response to radiation-induced oxidative damage might be an attempt to prevent genomic instability ( 43 ).…”
Section: Resultsmentioning
confidence: 99%